Optimasi Pengaruh Distribusi Cahaya terhadap Image Jual Produk pada Interior Domus Furniture and Home Decor, Surabaya - Carolina Siantoputri; Sumartono Sumartono; Poppy Firtatwentyna Nilasari (Intra, 2013)
Lighting is one of the important aspects in the interior of a retail shop. With adequate and even distribution of light as well as high-selling image, the products will look more interesting that consumers will be attracted to see them. This research was conducted to study that issue but will limit the discussion on artificial lighting.The research used quantitative and qualitative methods. The quantitative method was done by measuring the data in the field, questionnaire and optimization of artificial lighting whereas the qualitative method by literature, observation, interview and photo documentation. Analysis is done descriptively by comparing state of the field, literature and simulation. The result shows that the light distribution during the day is still less uniform than at night. Artificial lighting optimization was done by creating simulations with DIALux 4.7. program in 3 scenarios. The final scenario has already met the standard. Results of questionnaire and interview shows that lighting in Domus Furniture and Home Decor affect the selling image, because artificial lighting in the interior of Domus Furniture and Home Decor looks attractive, bright and the products are also more visible from the outside